1972
DOI: 10.1073/pnas.69.6.1517
|View full text |Cite
|
Sign up to set email alerts
|

Strand Orientation of Simian Virus 40 Transcription in Productively Infected Cells

Abstract: Strand orientation of transcription in BSC-1 cells infected by simian virus 40 (SV40) was investigated by annealing RNAs extracted from infected cells with asymmetric complementary RNA from SV4O DNA synthesized in vitro by RNA polymerase from Escherichia coli. The results suggest that the early viral RNA sequences (those made before replication of viral DNA) and the late RNA sequences (those synthesized concurrently with replication of viral DNA) are transcribed from opposite strands of the SV40 DNA. The RNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
0

Year Published

1972
1972
1978
1978

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 14 publications
3
31
0
Order By: Relevance
“…1 and 2). These results are in agreement with the data of D. Lindstrom and R. Dulbecco, who have recently shown that "early lytic" RNA has the same polarity as cRNA, while a significant portion of "late lytic" RNA is complementary to cRNA (13 One can only speculate about those modulating factors that bring about a switch to the plus strand after the initiation of viral DNA synthesis. One possibility would be the appearance of a new virus-specified RNA polymerase late in productive infection that can transcribe polynucleotide sequences on the plus strand.…”
Section: Discussionsupporting
confidence: 81%
“…1 and 2). These results are in agreement with the data of D. Lindstrom and R. Dulbecco, who have recently shown that "early lytic" RNA has the same polarity as cRNA, while a significant portion of "late lytic" RNA is complementary to cRNA (13 One can only speculate about those modulating factors that bring about a switch to the plus strand after the initiation of viral DNA synthesis. One possibility would be the appearance of a new virus-specified RNA polymerase late in productive infection that can transcribe polynucleotide sequences on the plus strand.…”
Section: Discussionsupporting
confidence: 81%
“…One class is present at both early and late times after infection and is complementary to about 30-35% of the E, or (-), strand of viral DNA. The second class, which becomes detectable only after SV40 DNA synthesis has begun, is com-plementary to about 65-70%o of the sequences of the L, or strand (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…The homology distribution of SV40 cRNA.-I between heavy and light strands of Ad2+ND1 is shown in Table 1B. Only the light strand has significant homology with this RNA, and the very small amount of hybridization exhibited by the heavy strand most likely arises from a small amount of symmetrical transcription during in vitro synthesis of the cRNA (9). This result confirms that the two DNA strands are well separated and, in addition, serves to identify the SV40 moiety present in the light strand of Ad2+ND, as a portion of thestrand of SV 40 DNA (early RNA template) (13 tidine (8).…”
mentioning
confidence: 99%
“…The entire genome is transcribed after viral DNA replication has begun., so that the RNA synthesized late in. infection conlists of both early and late sequences (early-plus-late RNA) (7)(8)(9). Although the strands of SV40 cannot be sel)arated with synthetic polyribonucleotides (10), Westphal (11) demonstrated that su)erhelical SV40 DNA (Form I) is transcribed asymmetrically (from one strand) by E. coli RNA polymerase in vitro.…”
mentioning
confidence: 99%